ANALISIS GAYA BAHASA IKLAN LAYANAN MASYARAKAT (ILM) TENTANG PANDEMI COVID-19 di YOUTUBE: LANGUAGE ANALYSIS OF COMMUNITY SERVICE ADS (PSAs) ABOUT COVID-19 PANDEMI on YOUTUBE - Rustang, Masita; Mayong; Sultan (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This research is entitled Analysis of the language style of public service advertisements (PSAs) about the Covid-19 pandemic on YouTube. This research is a descriptive qualitative research that aims to describe the style of language contained in Public Service Advertisements (PSAs) related to the Covid-19 Pandemic on Youtube. The style of language examined in public service advertisements about the Covid-19 pandemic on YouTube totals eight advertisements. The results of the study regarding the use of language style in PSAs related to covid-19 found by researchers are 28 data which are divided into six personifications, five anaphora, one alliteration, two asindetons, seven polysyndetons, four hyperboles, two similes, and one metaphor